Layout proposition to enhance production performance of pt. Mutiara jaya prahasta - Prawira, Pandu; P.K. Bintoro, Bambang (The Indonesian Journal of Business Administration, 2018)
Abstract – PT Jakarta International Container Terminal (JICT) is the first container terminal that has the most advanced equipment in Indonesia. PT JICT has experienced uptrend of import dwelling time using linear trend model has increased in from 2016 to 2017, as well as YOR. The situation in the field shows that the deposition or accumulation of containers might be prolonged which made dwelling time became longer and it affected the level of yard occupancy ratio (YOR). The methodology used in this research is Kepner – Tregoe (KT) Approach, which was supported by Cause and Effect Analysis (Fishbone Diagram) in problem analysis and Analytic Hierarchy Process (AHP) in decision analysis with six hierarchies used in this research based on the stakeholders which classified by governmental institutions including customs, regulator, and ministries and non-governmental institutions including PT JICT, importers, trucking and warehousing services. It includes the alternative option strategies: (a) Improving the quality of equipment, infrastructures and operational systems. (b) Creating Early Warning System model among stakeholders. (c) Optimizing internal trucking and warehousing. (d) Optimizing single window services. (e) Proposing regulations by evaluation from operational point of view. Based on the AHP, resulting Importer is the highest priority weight (0.308) which indicates that Importer is stakeholder that has the most impact in dwelling time issue. Followed by Ministries in the second priority (0.215). Third place is occupied by the Regulator (0.197). Then, Customs is prioritized on the fourth (0.116). Next, Trucking & Warehousing Services is prioritized on the fifth (0.073). While the last priority is PT JICT (0.056). Under overall alternative strategy priorities, creating Early Warning System model among stakeholders occupies the highest priority weight (0.317) which will be the most prioritized strategy in solving high dwelling time import containers in PT JICT. N.CO (Notification Cargo Owner) is an Early Warning System model that supports the container terminal in dealing with dwelling time issue.Keywords: Analytic Hierarchy Process (AHP), Decision Making, Dwelling Time, Kepner – Tregoe, Yard Occupancy Ratio (YOR)